Antibiotic and O2 Omissions and Errors in Hospitalized Patients - Brokalaki, Hero; Matziou, Vasiliki N.; Brokalaki, Eirene; Fildissis, George; Myrianthefs, Pavlos; Merkouris, Anastasios (My University, 2008)
The aim was to investigate medication errors regarding antibiotic and oxygen therapy in 2 different hospital types, respiratory versus general, in Greece. Oxygen and antibiotic errors were 27.4% and 16.9%, respectively. Errors by physicians and nurses were nearly the same type and rates. Oxygen errors were significantly higher in the General Hospital. The study confirmed that medication processes should be reevaluated to prevent medication errors, and educational programs and protocols should be used.